Social history and glaucoma progression: the effect of body mass index, tobacco and alcohol consumption on the rates of structural change in patients with glaucoma - Youssif, Asmaa A; Onyekaba, Ndidi-Amaka; Naithani, Rizul; Abdelazeem, Khaled; Fathalla, Ahmed M; Abdel‐Rhaman, Mohamed S; Jammal, Alessandro A; Medeiros, Felipe A (British journal of ophthalmology, 2024)
Background/aimsAlthough obesity, tobacco and alcohol consumption were linked to the progression of numerous chronic diseases, an association of these social history aspects with glaucoma progression is not yet determined. This study aims to investigate the effect of body mass index (BMI) and history of tobacco and alcohol use on the rates of retinal nerve fibre layer (RNFL) change over time in glaucoma patients.Methods2839 eyes of 1584 patients with glaucoma from the Duke Ophthalmic Registry were included. Patients had at least two spectral-domain optical coherency tomography (SD-OCT) tests over a minimum 6-month follow-up. Self-reported history of alcohol and tobacco consumption was extracted from electronic health records and mean BMI was calculated. Univariable and multivariable linear mixed models were used to determine the effect of each parameter on RNFL change over time.ResultsMean follow-up time was 4.7±2.1 years, with 5.1±2.2 SD-OCT tests per eye. 43% and 54% of eyes had tobacco or alcohol consumption history, respectively, and 34% were classified as obese. Higher BMI had a protective effect on glaucoma progression (0.014 µm/year slower per each 1 kg/m2 higher; p=0.011). Tobacco and alcohol consumption were not significantly associated with RNFL change rates (p=0.473 and p=0.471, respectively). Underweight subjects presented significantly faster rates of structural loss (−0.768 µm/year; p=0.002) compared with normal weight.ConclusionsIn a large clinical population with glaucoma, habits of tobacco and alcohol consumption showed no significant effect on the rates of RNFL change. Higher BMI was significantly associated with slower rates of RNFL loss.